KEANEKARAGAMAN HAYATI HUTAN KEMASYARAKATAN UNTUK MENDUKUNG PEMENUHAN KEBUTUHAN GIZI RUMAH TANGGA DI KABUPATEN LAMPUNG BARAT - Kelana Indah Susilawati; Yayuk Farida Baliwati; Siti Madanijah (Jurnal Gizi dan Pangan, 2008)
The Government of West Lampung District issued Social Forestry Program to address forest degradation problem that caused by illegal logging. Therefore, nutritional carrying capacity of Social Forestry was important to be analyzed to understand the advantage of Social Forestry for farmer. The objectives of this research were to 1) analyze the characteristics of farmer household, 2) analyze the commodity diversity of Social Forestry, 3) analyze nutritional carrying capacity of Social Forestry.The sample was 90 Social Forestry’s farmer households chosen by using purposive sampling method.  The result of the research shows that almost all samples are small family which has elementary school-education-level and are Sundanese and Javanese.The average size of land organizing of Social Forestry each household is 1.3 ha ranged 0.25-4 ha.  The commodity diversity organized by the farmer household (52.2%) is included in low category with ≤12 commodities. The average nutritional carrying capacity of Social Forestry is 2 754 kcal/cap/day. More than half (67.8%) of the sample has reach nutritional carrying capacity≥ 90% of ideal nutritional requirement.